PENGARUH FAKTOR INDIVIDU DAN KUALITAS FISIK UDARA TERHADAP PRODUKTIVITAS PETUGAS DI RSIA X PROBOLINGGO, JAWA TIMUR - Serlly Frida Drastyana; Diah Wijayanti Sutha; Anif Prasetyorini; Emilya Indahyati (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2026)
Poor hospital environmental quality will affect staff members' wellbeing and productivity. The aim of this study was to examine how individual variables and physical air quality affected workers' productivity at RSIA X Probolinggo, East Java. This study used a cross-sectional design and was an analytical observational study. The research was carried out between July and September of 2025. All staff members working in RSIA X's maternity and pediatric wards made up the study population. Some staff members from RSIA X's maternity and pediatric departments comprised the study's sample. Simple random sampling was the method employed. Work productivity was the dependent variable, while the independent variables were temperature, airflow velocity, air humidity, illumination, education, work motivation, and sick building syndrome. Multiple linear regression was used for data analysis. The results of this study show that the majority of employees were bachelor's degree holders (S1), had modest Sick Building Syndrome symptoms, and were moderately motivated and productive at work. The RSIA maternity and children's wards had air largely in compliance with quality criteria for temperature, airflow velocity, humidity, and illumination. While indoor humidity affects work productivity, indoor air quality (temperature, lighting, and airflow velocity) has no influence. Work motivation and Sick Building Syndrome symptoms affect productivity, whereas education does not.Keywords: hospital, productivity, indoor air quality, individual factors